ON NONRELATIVISTIC Q ¯Q POTENTIAL VIA THE WILSON LOOP IN GALILEAN SPACETIME - Haryanto M Siahaan (Research Report - Engineering Science, 2011)
We calculate the static Wilson loop from string/gauge correspondence to obtain theQ¯Q potential in nonrelativistic quantum field theory, i.e. CFT with Galilean symme-try. We analyze the convexity conditions13 for Q¯Q potential in this theory, and obtainrestrictions for the acceptable dynamical exponent z.Keywords: Wilson loop; Galilean symmetry; Q¯Q pair; potential; holography.